Hubungan Penggunaan Media Sosial Dengan Kesehatan Mental Remaja di SMA Negeri 1 Godean - Julianti, Sinta; Satriyandari, Yekti (Universitas Respati Indonesia, 2025)
The background to this research is based on the increasing use of social media among teenagers. The number of teenagers who access social media continues to increase, reaching 153 million. Excessive use of social media makes teenagers addicted. Uncontrolled use of social media will disrupt mental health. This study aims to analyze the relationship between social media use and the mental health of teenagers at SMA Negeri 1 Godean. The method used in this research is a quantitative approach by collecting data through questionnaires distributed to 139 respondents. The research results show that the majority of respondents use social media in the frequent category, and there is a significant proportion of teenagers who experience mental health disorders. Analysis using the Spearman Rank correlation test shows an rho value of 0.627 with a p-value of 0.000, which indicates a significant positive relationship between social media use and adolescent mental health. It is hoped that these findings will provide insight for parents, educators and researchers regarding the importance of managing social media use for adolescent mental health.